Contradições maranhenses: a Política de Regularização Fundiária Urbana (REURB) entre financeirização, clientelismo e cooptação - BANI, Emanuele (2023)
This thesis, formulated under the historical-dialectical materialism, analyzes some of the ways, through which the public policy of land regularization established by the Brazilian State, at the same time and contradictorily, focuses on the conditions of access of the popular classes to urban land for the purpose of housing construction, reiterates the legal regime of private land ownership, contributes to the configuration of substantively permeable boundaries between legal and illegal, reproducing inequalities and sustaining the circle of the unequal model of production of urban space. The land regularization emerged in Brazil in response to the strength of the construction of popular occupations of areas to live and to the growing popular pressure of the urban movements of the 1970s/1980s for housing and Urban Reform, land regularization was consolidated as one of the guidelines of the national urban policy, mainly from Law number. 10,257/2001 – named as Estatuto da Cidade, which legislates on urban instruments aimed at regularizing occupied urban territories, but excluded from legal land ownership. Considering this socio-political and legal context, through theoretical and documentary research, this thesis reconstitutes and demarcates determinations that relates the Federal Law no 13.465/2017 (Lei da REURB), current national regulatory framework for land regularization in rural and urban areas: 1) the systemic appropriation of land regularization, reinforced by pressures from financial capitalism, by the expansion of the internationalization of real estate markets and by the expansion of economical borders; 2) the recent policies of the World Bank on land control favorable to the ordering of state actions aimed at mass property registration, which makes it possible to transform the enormous Brazilian land stock into a financial asset. The relationships that allow apprehending the REURB as an strategic action are decisive for the insertion of Brazil in the circuits of financial capitalism and can, therefore, be analyzed as a project of adjustment of the Brazilian State to the pressures of international capital associated with class interests and business sectors, real estate and rentiers. In deepening these themes of analysis, emphasizing expressions of the effectiveness of the REURB in specific urban areas, this thesis, presenting as its central axis the land issue in Ilha do Maranhão, based on theoretical and documental research, direct observation, interviews and empirical evidence, characterizes the Programa Estadual de Regularização Fundiária Urbana, carried out in the Brazilian state of Maranhão in the Flavio Dino governments (2015-2021), highlighting institutional aspects, political strategies, clientelistic appropriations and subjects. The results of the investigation into this Program allow to demarcate recurrent relationships and contradictions in the “legalization” of the “illegal city”, which are expressed, on the one hand, by attention to the needs of economic accumulation and, on the other hand, by clientelistic and populist practices with the population. of urban occupations defined as beneficiaries. It was possible to concluded, therefore, that the REURB proposed by the Brazilian State to guarantee and expand the conditions of access to the right to housing, by overcoming the illegality in relation to land ownership, tends, due to the contradictions that are inherent to them, to aggravate the scenario of inequalities and disputes over land present in Brazilian cities.